Upaya Peningkatan Kepuasan Kerja dan Kinerja Karyawan Perguruan Tinggi Melalui Motivasi Intrinsik dan Ekstrinsik - Musoli Musoli; Majang Palupi (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2018)
This research aims at analyzing the infuence of intrinsic and extrinsic motivation toward work satisfaction and staff performance. The information gained from this research is crucial for the institution as a consideration to apply the increase of staff’ performance. The subject of this research is the permanent educational personnel staffs of universities in Daerah Istimewa Yogyakarta. The technique of sample collecting applies the census method. The method of data collecting using survey method by distributing the questionnaires involves 104 respondents. The data is analyzed using Structural Equation Modeling (SEM) which is run through AMOS 21 program as the analysis tool. The research findings show that intrinsic motivation and extrinsic motivation have positive influence toward the  work satisfaction. Then intrinsic motivation has a positif effect toward the work satisfaction, meanwhile extrinsic motivation does not have influence toward the work satisfaction, and the work satisfaction has a positive influence toward the work performance. Generally, this model is supported in field.